Forecasting Fuel Consumption Based-On OBD II Data - Satrio Nurcahya; Bayu Erfianto; Setyorini Setyorini (Indonesia Journal on Computing (Indo-JC), 2022)
Cyber Physical System consists of computing devices that communicate with each other by interacting with the physical world assisted by sensors and actuators with an iterative response. Intelligent Transportation System which aims to apply information and communication technology in every transportation area. Applying ITS to vehicles, especially in the aspect of fuel consumption, vehicles must begin to be able to analyze the use of fuel that is being used to provide users so that users can be more effective. Regarding the analysis of fuel consumption, several researchers have done this with several existing methods such as ANN, SVM and the like. The use of the Multivariate time series method is used as a solution to the forecast analysis of vehicle fuel consumption. In this study, data from vehicles obtained from OBD-II will be processed using the Multivariate time series method with output in the form of analysis and visual data from the forecast with parameters related to RPM, TPS and fuel consumption. So the expected result is the relationship between RPM, TPS and fuel consumption as well as the formation of a system model to obtain sample data related to RPM, TPS and fuel consumption.